DASAR LUAR ISLAM: PENYESUAIAN ANTARA TEORI FIQH TRADISIONAL DENGAN TUNTUTAN SEMASA - Mohamad, Mohd Nasran (Jurnal Syariah, 2019)
The central concern of this article is to review the concept of wo ld division as established by Medieval Muslim scholars especially f-!anafi School of Law who opined that the relation between Muslim territories (dar al[ shim) and Non-Muslim territories (dar al-harb) was continous warfare until either they become muslims or dhimmts. Whether this opinion still relevant to current world order is the main issue to be discussed in this article.